A new species of Fingeriana (Hemiptera: Cicadellidae: Cicadellini) - Rachel Alexandre de Carvalho; Rodney Ramiro Cavichioli (Zoologia (Curitiba), 2012)
Fingeriana reflexa sp. nov. is described and illustrated based on specimens collected in Camacan (Bahia) and Santa Teresa (Espírito Santo), Brazil. The new species can be distinguished from F. dubia Cavichioli, 2003 by the aedeagus narrowed towards the apex, with an apical pair of small triangular projections, and with a basal process laterally flattened and bent anteriorly on the apical portion. Notes comparing Fingeriana Cavichioli, 2003 to the similar Nielsonia Young, 1977 are provided.